Oral Health-Related Knowledge, Attitude and Practice among Nursing Students of Rohilkhand Medical College and Hospital: A Questionnaire Study - Kaira, Laxman Singh; Srivastava, Virag; Giri, Parul; Chopra, Devendra (Journal of Orofacial Research, 2012)
Aim: The present study was conducted to investigate the oral health knowledge, attitude and practice among nursing students of Rohilkhand Medical College and Hospital. Materials and methods: A questionnaire study was conducted among 111 nursing students of Rohilkhand Hospital who had an easy access to the dental services within the premises ofhospital itself. A self-administered structured questionnaire consisting of 32 questions on demographic data, oral hygiene knowledge, attitude and practices was distributed. The datacollected was analyzed using statistical package for social ciences (SPSS) version 11.5.Results and conclusion: A majority of the respondents were practicing healthy oral hygiene practices that included brushing twice a day with toothbrush and toothpaste for adequate duration of 2 to 3 minutes. Almost 87% of them were aware of the diseased gingival condition and the consequences due to accumulation of plaque. Almost half of the participants visited a dentist only on pain. However, a majority of them had given importance to their teeth equally as their general health. It was seen that the knowledge, attitude and practice of nursing students about oral health was adequate, but further improvements can be encouraged.